Pengaruh Penerapan Model Pembelajaran Inkuiri Sosial Pada Mata Pelajaran Pendidikan Agama Islam Terhadap Pengembangan Berpikir Kritis Siswa Di SMAN 14 Garut - Elin Merliana Amelia; Salamudin, Ceceng (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Critical thinking is essential in education as it enhances students' cognitive abilities during learning activities. However, critical thinking has not yet become a prevalent habit among students, resulting in some students being passive in the learning process, hesitant to express opinions, or ask questions. The social inquiry learning model in Islamic Education subjects is an approach that adapts to students' experiences, enabling them to find answers independently. Consequently, the social inquiry learning model can foster critical thinking in students. The purpose of this research is to describe the impact of the social inquiry learning model in Islamic Education subjects on the development of students' critical thinking skills. This will help determine the extent of the relationship between the application of the social inquiry learning model in Islamic Education subjects (Variable X) and the development of students' critical thinking skills (Variable Y). The method used in this research is the inferential quantitative method, which involves collecting data or information about the phenomenon being studied. Data collection techniques include questionnaires distributed to 25 respondents, observations, and documentation studies. Data processing was conducted through statistical data analysis. The research results show that the social inquiry learning model in Islamic Education subjects achieved a score of 4.056, placing it within the 3.01-4.00 interval range, classified as good. Meanwhile, the development of students' critical thinking skills had an average score of 3.976, also within the 3.01-4.00 interval range, classified as good. Based on statistical tests, there is an influence of the social inquiry learning model in Islamic Education subjects at 38.59%, while other factors influencing students' critical thinking skills account for 61.41% but were not examined in this study. Keywords : Social Inquiry Learning Model, Islamic Education Subject, Students' Critical Thinking